Strategy to Increase Brand Awareness of Kacandipa Micro, Small, and Medium Enterprises (MSMEs) Through Marketing Events in Sunju Village, Marawola District - Sandana, Charol Lorent; Ira Nuriyati; Ponirin; Muh. Zeylo A. (PT. Global World Scientific, 2025)
This study aims to explore the effectiveness of event marketing in increasing brand awareness of Kacandipa MSME products in Sunju Village, Marawola District. The study's results indicate that marketing events, particularly culinary folk festivals, have a significant impact on introducing products to consumers both locally and beyond the village. Before the event, Kacandipa products were less well-known, but after the event, there was a significant increase in demand, especially from outside the town. The use of promotional media, both offline through banners and flyers, and online through social media, has proven effective in expanding the market and introducing products more widely. This aligns with marketing theory, which states that combining conventional and digital marketing will increase brand awareness more effectively. In addition to increasing brand awareness, marketing events also have a positive impact on consumer loyalty. Many consumers feel a deeper connection to the product after hearing the story of Kacandipa's origins, which strengthens their emotional bond with the product. The use of social media in this event also opens up greater market opportunities for Kacandipa MSMEs. Although there are challenges related to limited funds and a lack of understanding of digital marketing among MSMEs, this study shows that with greater support from the village government and local communities, this event-based marketing strategy can provide significant long-term benefits for MSMEs and the village economy.